LITERATURE REVIEW : THE INFLUENCE OF JOB STRESS, WORKLOAD AND COMPENSATION ON GOJEK DRIVER PERFORMANCE IN BEKASI CITY - Nazwa Dea Devilia (Draf Solusi Indonesia, 2023)
This research is a literature review that discusses theinfluence of work stress, workload and compensationon the performance of online motorcycle taxis inBekasi City. This research uses several literaturestudies which will then build a model of therelationship between variables. This research willinvolve 62 online motorcycle taxi respondents inBekasi City, where the population in this study isunknown and the sample was taken using incidentaltechniques with the Lemeshow approach. SPSS bytesting the suitability of the data, namely validity andreliability tests and hypothesis testing, namely t and ftests and determination